Francisco Lindolfo Cordeiro na luta em defesa dos trabalhadores rurais do sertão cearense (1970-1978) - ALBUQUERQUE, Eline Ehrich (2016)
This work aims to analyze the performance of lawyer Francisco Lindolfo Cordeiro who, in the exercise of his profession. He became involved in agrarian struggles in the sertão of Ceará, in the political context of the military dictatorship, between 1970 and 1978. He was accused of inciting the workers Against landlords, was indicted as subversive in the National Security, Decree-Law 898 of September 29, 1969. He responded to the extensive and delaying process in the Military Justice. He when acquitted he was assassinated. In this sense, we make a theoretical approach under the study of politics in the perspective of the New Political History, considering that social and institutional practices may constitute political devices. In order to do so, we endeavor to contextualize the scenario of the struggles of rural workers in Ceará, during that period. Specifically, we will analyze the conflicts that occurred in the Japuara in farm, In the São Felipe Field and in the municipalities of Itatira and Maranguape, because they were objects of the accusation against Francisco Lindolfo Cordeiro, in order to analyze the causes of his indictment and the political context of his murder.